Light-shielding and moisture-proof container bag material and preparation method thereof

CN120307729BActive Publication Date: 2026-11-03NANTONG LIANRONG GRP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510470316.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-15
Publication Date
2026-11-03
Estimated Expiration
2045-04-15

AI Technical Summary

Technical Problem

Existing light-shielding and moisture-proof container bag materials pose a risk of heavy metal migration and low-molecular-weight substance transfer from organic moisture-proofing agents when in long-term contact with food. It is difficult to achieve stable fixation of light-shielding and moisture-proofing components in the polyolefin matrix, leading to foreign matter contamination.

Method used

It adopts a composite structure consisting of a light-shielding protective layer, a moisture-proof functional layer, a barrier reinforcement layer, and an inner contact layer. It uses materials such as ethylene-vinyl alcohol copolymer, grafted modified polyethylene, mitochondria-enriched mitochondria, and sulfonated modified SBS to form a tight microstructure through chemical bonding, physical entanglement, and interaction, which restricts molecular movement and material migration.

Benefits of technology

It improves the stability and safety of FIBC materials, reduces the migration rate of substances, and has good light-blocking and moisture-proof properties, thus protecting the safety and reliability of food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005359789010000091
    Figure BDA0005359789010000091
  • Figure BDA0005359789010000101
    Figure BDA0005359789010000101
Patent Text Reader

Abstract

The application relates to a light-shielding and moisture-proof container bag material and a preparation method thereof. The container bag material comprises a light-shielding and moisture-proof layer, a moisture-proof functional layer, a barrier strengthening layer and an inner contact layer. The material of the inner contact layer is polypropylene. The preparation raw materials of the barrier strengthening layer comprise the following components in mass fraction: ethylene-vinyl alcohol copolymer 30-40 parts, grafted modified polyethylene 20-30 parts, compatibilized nano-boehmite 10-15 parts, sulfonated modified SBS 3-8 parts and citric acid 0.5-1.5 parts. The container bag material prepared by the application has good light-shielding performance, moisture-proof performance and tensile performance. The substances in the material have low migration rate, and the application has good safety and reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of container bag technology, and in particular to a light-proof and moisture-proof container bag material and its preparation method. Background Technology

[0002] With the increasing demand for large-scale storage and transportation of rice and flour products, light-proof and moisture-proof container bags, as key packaging carriers, face stringent food contact safety requirements. Existing materials mostly adopt a multi-layer composite structure, achieving functional properties by adding light-proof masterbatch and moisture-proof coating. However, in practical applications involving long-term contact with food, it has been found that some inorganic light-proof fillers pose a risk of heavy metal migration, while organic moisture-proof additives are prone to the transfer of low molecular weight substances into the food matrix.

[0003] Current technological bottlenecks primarily stem from the interfacial compatibility issues between functional additives and food-grade substrates. Traditional melt blending processes struggle to achieve stable fixation of light-shielding components (such as titanium dioxide / carbon black) and moisture-proof components (such as nano-montmorillonite) within the polyolefin matrix. In fluctuating temperature and humidity transport environments, additive particles easily precipitate from the substrate surface, forming free substances that can penetrate the inner food contact film through friction or electrostatic adsorption, causing foreign matter contamination in rice and flour products. Therefore, improvements are needed. Summary of the Invention

[0004] To improve the stability of light-proof and moisture-proof container bags, this application provides a light-proof and moisture-proof container bag material and its preparation method.

[0005] This application provides a light-shielding and moisture-proof container bag material and its preparation method, which adopts the following technical solution: Firstly, this application provides a light-proof and moisture-proof container bag material, which adopts the following technical solution: A light-shielding and moisture-proof container bag material includes a light-shielding protective layer, a moisture-proof functional layer, a barrier reinforcement layer, and an inner contact layer. The inner contact layer is made of polypropylene, and the raw materials for preparing the barrier reinforcement layer include the following components in parts by weight: 30-40 parts of ethylene-vinyl alcohol copolymer 20-30 parts of grafted modified polyethylene Add 10-15 parts of Mibomstone 3-8 parts of sulfonated modified SBS Citric acid 0.5-1.5 parts.

[0006] The inner contact layer is made of polypropylene, which is resistant to chemical corrosion, ensures the safety of the contents, and has good mechanical strength, providing basic support for the whole structure. Ethylene-vinyl alcohol copolymer has good gas barrier properties, enhancing moisture resistance. Its molecular chains are intertwined with other polymers, which helps improve tensile strength, and its optical properties also improve light-blocking performance. Graft-modified polyethylene introduces new functional groups through grafting, enhancing compatibility with other components to optimize the microstructure, improving stability and tensile strength. Compatibilized mibohmite has nanoscale effects and a high specific surface area, enhancing tensile strength, adsorbing small molecules to improve moisture resistance, and after compatibilization modification, it can be uniformly dispersed, acting as a physical cross-linking point to enhance stability, enhance light scattering, and improve light-blocking performance. Sulfonation modification… SBS improves flexibility, reduces brittle fracture, and enhances tensile strength. Its unique molecular structure strengthens overall stability and synergistically optimizes the microstructure with other components, improving moisture resistance and light-blocking properties. Citric acid participates in the reaction during processing, regulating the process to promote the formation of a reasonable cross-linked structure between molecules, enhancing internal stability and comprehensively improving tensile strength, moisture resistance, and light-blocking properties, thus improving the stability of FIBC materials in complex environments. The components form a tight and orderly microstructure through chemical bonding, physical entanglement, and interaction, restricting molecular movement within the material, reducing diffusion channels caused by intermolecular gaps or defects, and inhibiting the migration of substances to food contact surfaces, giving FIBC materials good safety and reliability in food packaging applications.

[0007] Preferably, the raw materials for preparing the grafted modified polyethylene include polyethylene, hydroxyethyl acrylate, and vinyltrimethoxysilane.

[0008] Polyethylene provides good flexibility and strength; hydroxyethyl acrylate contains hydroxyl groups and double bonds, which can undergo grafting reactions with polyethylene molecular chains under the action of initiators. The introduced hydroxyl groups give the material a certain degree of polarity, enhancing its compatibility with other polar materials, improving the internal microstructure of the material, and improving overall stability. At the same time, this polarity helps to improve the adsorption capacity for small molecules, synergistically improving moisture-proof performance; the siloxy groups in vinyltrimethoxysilane can form silanol groups after hydrolysis, which then condense to form a siloxane network, enhancing the material's heat resistance and tensile strength; the double bonds of silane also participate in the grafting reaction, further optimizing the molecular structure, and the presence of the siloxane network hinders light propagation, thus improving light-shielding performance.

[0009] Preferably, the mass ratio of the polyethylene, hydroxyethyl acrylate and vinyltrimethoxysilane is 1:0.1:(0.25-0.35).

[0010] The grafted modified polyethylene prepared according to the above mass ratio has good light-blocking properties, moisture-proof properties and tensile properties.

[0011] Preferably, the raw materials for preparing the enriched microboehmite include nanoboehmite, silane coupling agent, and graphene oxide.

[0012] Nanoboehmite possesses a large specific surface area and good thermal stability, providing fundamental mechanical reinforcement for the material. Its crystal structure and nanoscale effect enhance light scattering and reduce light transmittance. The silanol groups at one end of the silane coupling agent molecule can undergo condensation reactions with the hydroxyl groups on the surface of nanoboehmite, while the organic functional groups at the other end can interact with other organic polymers, thus building a bridge between nanoboehmite and other material components, improving the dispersion and compatibility of nanoboehmite in the matrix, and enhancing the internal structural stability of the material. Graphene oxide has excellent mechanical properties, and its two-dimensional sheet structure can be uniformly dispersed in the system. It works synergistically with nanoboehmite to form physical cross-linking points within the material, improving tensile strength. The sheet structure of graphene oxide has a strong scattering and absorption effect on light, which can significantly enhance light-shielding performance. The hydrophobicity of graphene oxide and the adsorption properties of nanoboehmite work synergistically to effectively prevent water vapor penetration, further improving moisture-proof performance.

[0013] Preferably, the enlarged Mibohmite is prepared using the following steps: Nano-boehmite and silane coupling agent were dispersed in a solvent, heated and stirred to react, and after the reaction was completed, centrifuged, washed and dried to obtain surface-modified boehmite; graphene oxide and the surface-modified boehmite prepared above were mixed and ball-milled to obtain enriched micro-boehmite.

[0014] The enriched zeolite prepared according to the above steps has good dispersibility and compatibility, and can effectively improve the moisture-proof performance, light-blocking performance and tensile strength of the container bag material.

[0015] Preferably, the raw materials for preparing the sulfonated modified SBS include SBS matrix, chlorosulfonic acid, and hydrogenated rosin glycerol ester.

[0016] SBS possesses excellent flexibility and high elasticity. Chlorosulfonic acid, acting as a sulfonating agent, reacts with the SBS molecular chain, introducing sulfonic acid groups into the molecular structure. This imbues SBS with hydrophilicity and ionicity, improving its compatibility with other polar materials, promoting interactions between internal components, and enhancing overall stability. Furthermore, its ability to form hydrogen bonds with water molecules improves moisture resistance to some extent. The addition of hydrogenated rosin glycerol plays a dual role in plasticizing and reinforcing. Its long-chain structure inserts into the SBS molecular chain, improving the material's flexibility and making the FIBC (Flexible Intermediate Bulk Container) easier to bend and less prone to breakage during use, further enhancing tensile strength. Simultaneously, the conjugated double bond structure in hydrogenated rosin glycerol can absorb specific wavelengths of light, synergistically enhancing the light-blocking effect of the FIBC with other light-blocking components.

[0017] Preferably, the mass ratio of the SBS matrix, chlorosulfonic acid and hydrogenated rosin glycerol ester is 1:0.12:(0.4-0.5).

[0018] The sulfonated modified SBS prepared according to the above mass ratio can effectively improve the light-blocking performance, moisture-proof performance and tensile properties of the material.

[0019] Preferably, the light-shielding protective layer comprises an aluminized polyester film.

[0020] Polyester film possesses excellent mechanical properties and chemical stability. The aluminizing process forms a thin and uniform aluminum layer on the film surface. Aluminum has excellent optical reflection properties, which can efficiently reflect various types of light, such as visible light, ultraviolet light, and infrared light. This significantly reduces the light energy received by the food inside the container bag, effectively preventing problems such as food oxidation, discoloration, and nutrient loss caused by light exposure, and improving the light-blocking performance of the container bag. At the same time, the aluminum layer also has certain barrier properties, which can block the penetration of some gases and moisture, further enhancing the moisture-proof performance in conjunction with other layers.

[0021] Preferably, the moisture-proof functional layer comprises a polyvinylidene chloride coated polyester film.

[0022] Polyvinylidene chloride (PVDC) has a compact molecular structure containing a large number of chlorine atoms. The high electronegativity of chlorine atoms results in strong intermolecular forces, forming a highly dense molecular arrangement. This dense structure has a strong barrier effect against water molecules, making it difficult for water molecules to penetrate the PVDC coating. This effectively prevents external moisture from entering the interior of the container bag, significantly improving its moisture-proof performance. At the same time, the PVDC coating has chemical stability, which can resist the corrosion of chemical substances in the environment, enhancing the durability and stability of the moisture-proof functional layer.

[0023] Secondly, this application provides a method for preparing a light-shielding and moisture-proof container bag material, which adopts the following technical solution: A method for preparing a light-shielding and moisture-proof container bag material includes the following steps: Ethylene-vinyl alcohol copolymer, grafted modified polyethylene, octane-enriched mibohmite and sulfonated modified SBS are stirred and mixed to obtain a mixture; the mixture is heated and melted, citric acid is added in batches, stirred and reacted, extruded and air-cooled to obtain a barrier reinforcement layer; The hot melt adhesive is heated to melt, and the molten hot melt adhesive is evenly applied to the bonding surfaces of the two materials to be bonded. After bonding, pressure is applied to complete the bonding of the light-shielding protective layer, the moisture-proof functional layer, the barrier reinforcement layer and the inner contact layer in sequence, thus obtaining the light-shielding and moisture-proof container bag material.

[0024] The light-shielding and moisture-proof container bag material prepared according to the above steps is safe and environmentally friendly. The material has a tight cross-linking structure and a stable microstructure, which reduces the migration rate of substances. Its good light-shielding and moisture-proof properties enable it to effectively protect the contents and meet the needs of food storage and transportation.

[0025] In summary, this application includes at least one of the following beneficial technical effects: 1. The inner contact layer is made of polypropylene, which is resistant to chemical corrosion, ensures the safety of the contents, and has good mechanical strength, providing basic support for the whole structure. Ethylene-vinyl alcohol copolymer has good gas barrier properties, enhancing moisture resistance. Its molecular chains are intertwined with other polymers, which is beneficial for improving tensile strength, and its optical properties also improve light-blocking performance. Graft-modified polyethylene introduces new functional groups through grafting, enhancing compatibility with other components to optimize the microstructure, improving stability and tensile strength. Compatibilized microbubble has a nanoscale effect and high specific surface area, which can enhance tensile strength, adsorb small molecules to improve moisture resistance, and after compatibilization modification, it can be uniformly dispersed, acting as a physical cross-linking point to enhance stability, enhance light scattering, and improve light-blocking performance. Sulfonation... Modified SBS improves flexibility, reduces brittle fracture, and enhances tensile strength. Its unique molecular structure strengthens overall stability and synergistically optimizes the microstructure with other components, improving moisture resistance and light-blocking properties. Citric acid participates in the reaction during processing, regulating the process to promote the formation of a reasonable cross-linked structure between molecules, enhancing internal stability and comprehensively improving tensile strength, moisture resistance, and light-blocking properties, thus improving the stability of FIBC materials in complex environments. The components form a tight and orderly microstructure through chemical bonding, physical entanglement, and interaction, restricting molecular movement within the material, reducing diffusion channels caused by intermolecular gaps or defects, and inhibiting the migration of substances to food contact surfaces, giving FIBC materials good safety and reliability in food packaging applications.

[0026] 2. Polyethylene provides good flexibility and strength; hydroxyethyl acrylate contains hydroxyl groups and double bonds, which can undergo grafting reactions with polyethylene molecular chains under the action of initiators. The introduced hydroxyl groups give the material a certain degree of polarity, enhancing its compatibility with other polar materials, improving the internal microstructure of the material, and improving overall stability. At the same time, this polarity helps to improve the adsorption capacity for small molecules, synergistically improving moisture-proof performance; the siloxy groups in vinyltrimethoxysilane can form silanol groups after hydrolysis, which then condense to form a siloxane network, enhancing the material's heat resistance and tensile strength; the double bonds of silane also participate in the grafting reaction, further optimizing the molecular structure, and the presence of the siloxane network hinders light propagation, thus improving light-shielding performance.

[0027] 3. SBS possesses excellent flexibility and high elasticity. Chlorosulfonic acid, acting as a sulfonating agent, reacts with the SBS molecular chain, introducing sulfonic acid groups into the molecular structure. This imbues SBS with hydrophilicity and ionicity, improving its compatibility with other polar materials, promoting interactions between internal components, and enhancing overall stability. Furthermore, its ability to form hydrogen bonds with water molecules improves moisture resistance to some extent. The addition of hydrogenated rosin glycerol plays a dual role in plasticizing and reinforcing. Its long-chain structure inserts into the SBS molecular chain, improving the material's flexibility, making the FIBC (Flexible Intermediate Bulk Container) easier to bend and less prone to breakage during use, further enhancing tensile strength. Simultaneously, the conjugated double bond structure in hydrogenated rosin glycerol can absorb specific wavelengths of light, synergistically enhancing the light-blocking effect of the FIBC with other light-shielding components. Detailed Implementation

[0028] This application discloses a light-shielding and moisture-proof container bag material and its preparation method. Unless otherwise specified, all raw materials used in this application can be obtained from commercially available sources. The following detailed description, in conjunction with embodiments, further illustrates this application: Raw material specifications: Polyethylene (CAS No.: 9002-88-4), molecular weight 200,000; Hydroxyethyl acrylate (CAS No.: 818-61-1); Vinyltrimethoxysilane (CAS No.: 2768-02-7); Benzoyl peroxide (CAS No.: 94-36-0); Nano-boehmite (CAS No.: 1318-23-6), particle size 75nm; Silane coupling agent KH550 (CAS No.: 919-30-2); Graphene oxide (CAS No.: 7782-42-5), purchased from Shanghai Keyi Chemical Technology Co., Ltd. The product contains SBS (CAS No.: 873-55-2), with a molecular weight of 100,000; chlorosulfonic acid (CAS No.: 7790-94-5); hydrogenated rosin glycerol ester (CAS No.: 65997-13-9); ethylene-vinyl alcohol copolymer (CAS No.: 25067-34-9), with a molecular weight of 50,000; citric acid (CAS No.: 77-92-9); the hot melt adhesive is model Knorr King 1108FDA-HA; the light-shielding protective layer material is aluminized polyester film; the moisture-proof functional layer material is polyvinylidene chloride coated polyester film; and the inner contact layer is polypropylene.

[0029] Example 1 Preparation of graft-modified polyethylene 37.04g of polyethylene was heated to 160℃ and stirred at 400rpm. After the polyethylene was completely melted, 3.7g of hydroxyethyl acrylate, 9.26g of vinyltrimethoxysilane and 0.1g of benzoyl peroxide were added. The mixture was stirred at 160℃ and 400rpm for 2 hours. After the reaction was completed, the mixture was cooled to below 30℃, granulated and discharged to obtain grafted modified polyethylene.

[0030] Preparation of Mibohmite with increased capacity 19.8 g of nano-boehmite and 0.6 g of silane coupling agent KH550 were added to 150 mL of anhydrous ethanol and ultrasonically dispersed for 30 min. The mixture was stirred at 60 °C for 3 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, and dried at 60 °C to obtain surface-modified boehmite. 0.2 g of graphene oxide and the surface-modified boehmite prepared above were added to a ball mill and ball-milled at 300 rpm for 5 h to obtain enlarged-capacity micro-boehmite.

[0031] Preparation of sulfonated modified SBS 6.58 g of SBS was heated to 150 °C and stirred at 200 rpm. 0.79 g of chlorosulfonic acid was added dropwise over 1 hour. The mixture was stirred at 150 °C and 200 rpm for 2 hours. Then, 2.63 g of hydrogenated rosin glycerol ester was added, the temperature was raised to 150 °C, and the mixture was stirred at 300 rpm for 3 hours. After the reaction was completed, the product was neutralized in sodium hydroxide solution. After cooling to below 30 °C, the mixture was filtered, washed with deionized water, and dried at 60 °C to obtain sulfonated modified SBS.

[0032] Preparation of light-proof and moisture-proof container bag materials 30g of ethylene-vinyl alcohol copolymer, 20g of grafted modified polyethylene, 10g of compatibilized mibohmite and 3g of sulfonated modified SBS were mixed and stirred at 1000rpm for 15min to obtain a mixture. The mixture was added to a twin-screw extruder and heated to melt in three zones: 150℃ in zone 1, 170℃ in zone 2 and 190℃ in zone 3. At a screw speed of 200rpm, 0.5g of citric acid was added in three batches every 5min, starting in zone 2. After stirring and reacting for 20min, the mixture was extruded through a die and air-cooled to 40℃ to obtain a barrier reinforcement layer with a thickness of 0.1mm.

[0033] The hot-melt adhesive is heated to 180°C using a heating roller to melt it. The molten hot-melt adhesive is then evenly applied to the surfaces of the two materials to be bonded, with the application amount controlled at 20g / m². 2 After lamination, the material is held under 0.3MPa pressure for 10 seconds to sequentially complete the lamination of the light-shielding protective layer, the moisture-proof functional layer, the barrier reinforcement layer, and the inner contact layer, thus obtaining the light-shielding and moisture-proof container bag material.

[0034] Example 2 Preparation of graft-modified polyethylene 34.48g of polyethylene was heated to 160℃ and stirred at 400rpm. After the polyethylene was completely melted, 3.45g of hydroxyethyl acrylate, 12.07g of vinyltrimethoxysilane and 0.1g of benzoyl peroxide were added. The mixture was stirred at 160℃ and 400rpm for 2 hours. After the reaction was completed, the mixture was cooled to below 30℃, granulated and discharged to obtain grafted modified polyethylene.

[0035] Preparation of Mibohmite with increased capacity 19.8 g of nano-boehmite and 0.6 g of silane coupling agent KH550 were added to 150 mL of anhydrous ethanol and ultrasonically dispersed for 30 min. The mixture was stirred at 60 °C for 3 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, and dried at 60 °C to obtain surface-modified boehmite. 0.2 g of graphene oxide and the surface-modified boehmite prepared above were added to a ball mill and ball-milled at 300 rpm for 5 h to obtain enlarged-capacity micro-boehmite.

[0036] Preparation of sulfonated modified SBS 6.17 g of SBS was heated to 150 °C and stirred at 200 rpm. 0.74 g of chlorosulfonic acid was added dropwise over 1 hour. The mixture was stirred at 150 °C and 200 rpm for 2 hours. Then, 3.09 g of hydrogenated rosin glycerol ester was added, the temperature was raised to 150 °C, and the mixture was stirred at 300 rpm for 3 hours. After the reaction was completed, the product was neutralized in sodium hydroxide solution. After cooling to below 30 °C, the mixture was filtered, washed with deionized water, and dried at 60 °C to obtain sulfonated modified SBS.

[0037] Preparation of light-proof and moisture-proof container bag materials 40g of ethylene-vinyl alcohol copolymer, 30g of grafted modified polyethylene, 15g of compatibilized mibohmite and 8g of sulfonated modified SBS were mixed and stirred at 1000rpm for 15min to obtain a mixture. The mixture was added to a twin-screw extruder and heated to melt in three zones: 150℃ in zone 1, 170℃ in zone 2 and 190℃ in zone 3. At a screw speed of 200rpm, 1.5g of citric acid was added in three batches every 5min, starting in zone 2. After stirring and reacting for 20min, the mixture was extruded through a die and air-cooled to 40℃ to obtain a barrier reinforcement layer with a thickness of 0.1mm.

[0038] The hot-melt adhesive is heated to 180°C using a heating roller to melt it. The molten hot-melt adhesive is then evenly applied to the surfaces of the two materials to be bonded, with the application amount controlled at 20g / m². 2 After lamination, the material is held under 0.3MPa pressure for 10 seconds to sequentially complete the lamination of the light-shielding protective layer, the moisture-proof functional layer, the barrier reinforcement layer, and the inner contact layer, thus obtaining the light-shielding and moisture-proof container bag material.

[0039] Example 3 Preparation of graft-modified polyethylene 35.71g of polyethylene was heated to 160℃ and stirred at 400rpm. After the polyethylene was completely melted, 3.57g of hydroxyethyl acrylate, 10.72g of vinyltrimethoxysilane and 0.1g of benzoyl peroxide were added. The mixture was stirred at 160℃ and 400rpm for 2 hours. After the reaction was completed, the mixture was cooled to below 30℃, granulated and discharged to obtain grafted modified polyethylene.

[0040] Preparation of Mibohmite with increased capacity 19.8 g of nano-boehmite and 0.6 g of silane coupling agent KH550 were added to 150 mL of anhydrous ethanol and ultrasonically dispersed for 30 min. The mixture was stirred at 60 °C for 3 h. After the reaction was completed, the mixture was centrifuged, washed with deionized water, and dried at 60 °C to obtain surface-modified boehmite. 0.2 g of graphene oxide and the surface-modified boehmite prepared above were added to a ball mill and ball-milled at 300 rpm for 5 h to obtain enlarged-capacity micro-boehmite.

[0041] Preparation of sulfonated modified SBS 6.37 g of SBS was heated to 150 °C and stirred at 200 rpm. 0.76 g of chlorosulfonic acid was added dropwise over 1 hour. The mixture was stirred at 150 °C and 200 rpm for 2 hours. Then, 2.87 g of hydrogenated rosin glycerol ester was added, the temperature was raised to 150 °C, and the mixture was stirred at 300 rpm for 3 hours. After the reaction was completed, the product was neutralized in sodium hydroxide solution. After cooling to below 30 °C, the mixture was filtered, washed with deionized water, and dried at 60 °C to obtain sulfonated modified SBS.

[0042] Preparation of light-proof and moisture-proof container bag materials 35g of ethylene-vinyl alcohol copolymer, 25g of grafted modified polyethylene, 12.5g of compatibilized mibohmite and 5.5g of sulfonated modified SBS were mixed and stirred at 1000rpm for 15min to obtain a mixture. The mixture was added to a twin-screw extruder and heated to melt in three zones: 150℃ in zone 1, 170℃ in zone 2 and 190℃ in zone 3. At a screw speed of 200rpm, 1g of citric acid was added in three batches every 5min, starting in zone 2. After stirring and reacting for 20min, the mixture was extruded through a die and air-cooled to 40℃ to obtain a barrier reinforcement layer with a thickness of 0.1mm.

[0043] The hot-melt adhesive is heated to 180°C using a heating roller to melt it. The molten hot-melt adhesive is then evenly applied to the surfaces of the two materials to be bonded, with the application amount controlled at 20g / m². 2After lamination, the material is held under 0.3MPa pressure for 10 seconds to sequentially complete the lamination of the light-shielding protective layer, the moisture-proof functional layer, the barrier reinforcement layer, and the inner contact layer, thus obtaining the light-shielding and moisture-proof container bag material.

[0044] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of polyethylene used is 40g, the amount of hydroxyethyl acrylate is 4g, and the amount of vinyltrimethoxysilane is 6g.

[0045] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of polyethylene is 32.26g, the amount of hydroxyethyl acrylate is 3.23g, and the amount of vinyltrimethoxysilane is 14.51g.

[0046] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that hydroxyethyl acrylate is not added when preparing grafted modified polyethylene in Example 6.

[0047] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that graphene oxide is not added when preparing the enriched Mibomite in Example 7.

[0048] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the amount of SBS is 7.04g, the amount of chlorosulfonic acid is 0.85g, and the amount of hydrogenated rosin glycerol ester is 2.11g.

[0049] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the amount of SBS is 5.81g, the amount of chlorosulfonic acid is 0.7g, and the amount of hydrogenated rosin glycerol ester is 3.49g.

[0050] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that chlorosulfonic acid is not added when preparing sulfonated modified SBS in Example 10.

[0051] Comparative Example 1 Comparative Example 1 is based on Example 3. The only difference between Comparative Example 1 and Example 3 is that the grafted modified polyethylene is replaced with polyethylene in Comparative Example 1.

[0052] Comparative Example 2 Comparative Example 2 is based on Example 3. The only difference between Comparative Example 2 and Example 3 is that Comparative Example 2 replaces the superimposed microboehmite with nanoboehmite.

[0053] Comparative Example 3 Comparative Example 3 is based on Example 3. The only difference between Comparative Example 3 and Example 3 is that sulfonated modified SBS is replaced with SBS in Comparative Example 3.

[0054] Performance testing (1) Select GB / T10454-2000 FIBC as the standard, test the tensile strength of the specimens, prepare three samples for each specimen, take the average value after measurement, and record the results in Table 1.

[0055] (2) Shielding test: Cut the sample into a suitable size and put it into the sample cell. Using air as a reference, test and calculate the transmittance of visible light. Test each sample three times, take the average value after measurement, and record the results in Table 1.

[0056] (3) Select GB / T1037-1988 Test method for water vapor permeability of plastic films and sheets (cup method) as the standard. Seal the sample on the permeable cup, fill the cup with water, and place the side of the sample that does not contact the food facing the water. Place the permeable cup in an environment of 38℃ and 90% humidity for 24 hours, weigh the weight change of the permeable cup, and calculate the water vapor permeation. Prepare three samples for each sample, take the average value after measurement, and record the results in Table 1.

[0057] (4) Using GB31604.8-2021 National Food Safety Standard for Determination of Total Migration of Food Contact Materials and Articles as the standard, the sample was cut into 100cm pieces. 2 For the samples, 10% ethanol was used as a food simulant. The samples were sealed and soaked for 10 days. After soaking, the samples were removed, the soaking solution was rotary evaporated, and the samples were transferred to glass petri dishes and dried to constant weight. The total mass of the petri dishes and the residue after drying was weighed, and the migration amount per unit area of ​​the sample was calculated. Three samples were prepared for each test, and the average value was taken after measurement. The results are recorded in Table 1.

[0058] Table 1. Test results of tensile properties, light-blocking properties, moisture-proof properties, and migration rate of FIBC materials. As shown in Table 1, the tensile strength of Examples 1-3 is greater than 38.72 MPa, the light transmittance is less than 0.6%, and the water vapor transmission rate is less than 1.3 g / (m²). 2 •d), migration amount less than 0.95 mg / dm 2 This demonstrates that the container bag material prepared in this application has good tensile strength, light-blocking properties, moisture-proof properties, and low migration rate.

[0059] As shown in Table 1, the differences between Examples 4, 5, and 6 and Example 3 are only as follows: In Example 4, the mass ratio of polyethylene, hydroxyethyl acrylate, and vinyltrimethoxysilane is 1:0.1:0.15; in Example 5, the mass ratio of polyethylene, hydroxyethyl acrylate, and vinyltrimethoxysilane is 1:0.1:0.45; and in Example 6, hydroxyethyl acrylate is not added when preparing the grafted modified polyethylene. Compared with Example 3, the performance of Examples 4, 5, and 6 is somewhat reduced. This is because the optimal component ratio is disrupted, affecting the synergistic effect between the components; the lack of hydroxyethyl acrylate further affects the synergistic effect between the components, affecting the microstructure of the material and reducing the overall stability.

[0060] As shown in Table 1, the only difference between Example 7 and Example 3 is that graphene oxide was not added when preparing the nanoboehmite in Example 7. Compared with Example 3, the performance of Example 7 decreased. This is because the lack of graphene oxide resulted in the absence of the synergistic effect between nanoboehmite and graphene oxide, weakening the reinforcing effect and reducing the dispersibility and compatibility of nanoboehmite, thus affecting the performance of the container bag material.

[0061] As shown in Table 1, the differences between Examples 8, 9, and 10 and Example 3 are only as follows: In Example 8, the mass ratio of SBS, chlorosulfonic acid, and hydrogenated rosin glycerol ester is 1:0.12:0.3; in Example 9, the mass ratio of SBS, chlorosulfonic acid, and hydrogenated rosin glycerol ester is 1:0.12:0.6; and in Example 10, chlorosulfonic acid is not added when preparing sulfonated modified SBS. Compared with Example 3, the performance of Examples 8, 9, and 10 is somewhat reduced. This is because the optimal ratio is disrupted, affecting the synergistic effect between the components in the sulfonated modified SBS; the absence of chlorosulfonic acid reduces the compatibility between components, making it easier for moisture to penetrate and thus reducing performance.

[0062] As shown in Table 1, the only difference between Comparative Example 1 and Example 3 is that the grafted modified polyethylene was replaced with polyethylene in Comparative Example 1. Compared with Example 3, the performance of Comparative Example 1 is significantly reduced. This is because polyethylene lacks modification treatment, the compatibility between components decreases, and interface defects are easily caused, resulting in a significant decrease in tensile properties, moisture resistance and light-blocking properties.

[0063] As shown in Table 1, the only difference between Comparative Example 2 and Example 3 is that the superimposed microboehmite was replaced with nanoboehmite in Comparative Example 2. Compared with Example 3, the performance of Comparative Example 2 is significantly reduced. This is because nanoboehmite lacks modification treatment, resulting in decreased dispersibility and compatibility, and it is prone to agglomeration, thus affecting the performance of the container bag material.

[0064] As shown in Table 1, the only difference between Comparative Example 3 and Example 3 is that sulfonated modified SBS was replaced with SBS in Comparative Example 3. Compared with Example 3, the performance of Comparative Example 3 is significantly reduced. This is because without modification of SBS, the compatibility between components decreases, thereby affecting the stability of the material and the performance of the FIBC material is significantly reduced.

[0065] This specific embodiment is merely an explanation of this application and is not intended to limit it. Based on the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of this application. The technical scope of this application is not limited to the contents of the specification but must be determined according to the scope of the claims.

Claims

1. A light-proof and moisture-proof container bag material, characterized in that: It includes a light-shielding protective layer, a moisture-proof functional layer, a barrier reinforcement layer, and an inner contact layer. The inner contact layer is made of polypropylene, and the raw materials for preparing the barrier reinforcement layer include the following components in parts by weight: 30-40 parts of ethylene-vinyl alcohol copolymer 20-30 parts of grafted modified polyethylene Add 10-15 parts of Mibomstone 3-8 parts of sulfonated modified SBS Citric acid 0.5-1.5 parts; The raw materials for preparing the grafted modified polyethylene include polyethylene, hydroxyethyl acrylate and vinyltrimethoxysilane; The raw materials for preparing the enriched microboehmite include nanoboehmite, silane coupling agent and graphene oxide; The enriched Mibohmite was prepared using the following steps: Nano-boehmite and silane coupling agent were dispersed in a solvent, heated and stirred to react, and after the reaction was completed, centrifuged, washed and dried to obtain surface-modified boehmite; graphene oxide and the surface-modified boehmite prepared above were mixed and ball-milled to obtain enriched micro-boehmite; The raw materials for preparing the sulfonated modified SBS include SBS matrix, chlorosulfonic acid, and hydrogenated rosin glycerol ester.

2. The light-shielding and moisture-proof container bag material according to claim 1, characterized in that: The mass ratio of the polyethylene, hydroxyethyl acrylate and vinyltrimethoxysilane is 1:0.1:(0.25-0.35).

3. The light-shielding and moisture-proof container bag material according to claim 1, characterized in that: The mass ratio of the SBS matrix, chlorosulfonic acid, and hydrogenated rosin glycerol ester is 1:0.12:(0.4-0.5).

4. The light-shielding and moisture-proof container bag material according to claim 1, characterized in that: The light-shielding protective layer includes an aluminized polyester film.

5. The light-shielding and moisture-proof container bag material according to claim 1, characterized in that: The moisture-proof functional layer comprises a polyvinylidene chloride coated polyester film.

6. A method for preparing a light-shielding and moisture-proof container bag material as described in any one of claims 1-5, characterized in that: Includes the following steps: Ethylene-vinyl alcohol copolymer, grafted modified polyethylene, octane-enriched mibohmite and sulfonated modified SBS are stirred and mixed to obtain a mixture; the mixture is heated and melted, citric acid is added in batches, stirred and reacted, extruded and air-cooled to obtain a barrier reinforcement layer; The hot melt adhesive is heated to melt, and the molten hot melt adhesive is evenly applied to the bonding surfaces of the two materials to be bonded. After bonding, pressure is applied to complete the bonding of the light-shielding protective layer, the moisture-proof functional layer, the barrier reinforcement layer and the inner contact layer in sequence, thus obtaining the light-shielding and moisture-proof container bag material.

Citation Information

Patent Citations

  • Polypropylene resin composition, molded article produced from the resin composition, and method for production of the molded article

    CN101910287A

  • Hydrophobic surface modified aluminas for polymer compositions and method for making thereof

    CN108368355A